Neurosurgical Spine Implants in Geriatric Patients Treated Surgically for Lumbar Stenosis - Zygmunt Siedlecki; Emilia Główczewska-Siedlecka; Małgorzata Szafrańska; Maciej Śniegocki (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. The incidence of degenerative lumbar spine stenosis increases with age. While young people tend to have simple disc herniations with root compression, older people develop degenerative stenosis: facet joint hypertrophy, osteophytes, and ligamentum flavum hypertrophy. A typical for senility is neurogenic claudication caused by lumbar foraminal stenosis. Its symptoms decrease in spine flexion. Aim. The study consisted of a retrospective evaluation of medical data: analysis of the patient’s age, description of the surgical procedure and a list of spine implants. Material and Methods. The analysis included patients treated surgically for lumbar stenosis in 2020 in Neurosurgical Department of Collegium Medicum in Nicolaus Copernicus University (Bydgoszcz, Poland). Results. The perioperative risk increases with the age of patients, therefore procedures in elderly patients should usually be less invasive, ephemeral, and even under local anesthesia. Therefore, neurosurgeons tend to insert spinal implants in senility to support the surgical effect and optimize the time of the procedure. Interspinous spacers are implants for neurogenic claudication. Interspinous spacers causes foraminal distraction and thus can theoretically induce nerve roots decompression in indirect mechanism, less invasive, with less tissue damage. We notice significantly more frequent use of interspinous spacers in patients over seventy. Conclusions. This observation requires further research and analysis; however, it is consistent with the available literature and the actual state of clinical practice. This has potentially important implications for neurosurgical nursing — in geriatric patients after lumbar spine surgery, implants are significantly more common — interspinous spacers, which should be considered in nursing perioperative recommendations. (JNNN 2021;10(3):91–95)